Improving fertilizer response of crop yield through liming and targeting to landscape positions in tropical agricultural soils - Agegnehu, Getachew; Amede, Tilahun; Desta, Gizaw; Erkossa, Teklu; Legesse, Gizachew; Gashaw, Tadesse; Rooyen, Andre van; Harawa, Rebbie; Degefu, Tulu; Mekonnen, Kindu; Schulz, Steffen (Elsevier, 2023)
Nutrient management research was conducted across locations to investigate the influence of landscape position (hill, mid-, and foot slope) in teff (Eragrostis tef) and wheat (Triticum aestivum) yield response to fertilizer application and liming in the 2018 and 2019 cropping seasons. The treatments included 1) NPS fertilizer as a control treatment (42 N + 10P + 4.2S kg ha−1 for teff and 65 N + 20P + 8.5S kg ha−1 for wheat); 2) NPS and potassium (73 N + 17P + 7.2S + 24 K kg ha−1 for teff and 103 N + 30P + 12.7S + 24 K kg ha−1 for wheat) and 3) NPSK and zinc (73 N + 17P + 7.2S + 24K + 5.3Zn kg ha−1 for teff and 103 N + 30P + 12.7S + 24K + 5,3Zn kg ha−1 for wheat) in acid soils with and without liming. Results showed that the highest teff and wheat grain yields of 1512 and 4252 kg ha−1 were obtained at the foot slope position, with the respective yield increments of 71% and 57% over the hillslope position. Yield response to fertilizer application significantly decreased with increasing slope owing to the decrease in soil organic carbon and soil water content and the increase in soil acidity. The application of lime with NPSK and NPSKZn fertilizer increased teff and wheat yields by 43–54% and 32–35%, respectively compared to the application of NPS fertilizer without liming where yield increments were associated with the application of N and P nutrients. Orthogonal contrasts revealed that landscape position, fertilizer application, and their interaction effects were significant on teff and wheat yields. Soil properties including soil pH, organic carbon, total N, and soil water content were increased down the slope, which might be attributed to sedimentation down the slope. However, available P is yet very low both in acidic and non-acidic soils. We conclude that crop response to applied nutrients could be enhanced by targeting nutrient management practices to agricultural landscape features and addressing other yield-limiting factors such as soil acidity and nutrient availability by conducting further research.